I Keep Looking at What I'm Doing to My Organs: Samoans' Responses to Adapted Anti-Tobacco Television Advertisements. (September 2021) - Umali, Elaine; Tanielu, Helen; Whittaker, Robyn; Sugden, Cam; McCool, Judith
There has been an increase of adapted tobacco control media campaigns in low- and middle-income countries. Adapting existing material offers many benefits especially to countries with limited resources. We adapted 3 television advertisements for the Tu'u Nei Loa Le Ulaula Tapa'a (Stop Smoking Now) campaign in Samoa. Adaption included rigorous efforts to ensure advertisements were culturally appropriate. To determine audiences' perception of anti-tobacco television advertisements to promote smoking cessation, we conducted 8 talanoa, a Pacific Islands research methodology, among 54 smokers and nonsmokers in Apia, Samoa. The talanoa were transcribed, translated, and thematically coded. Results suggest that the advertisements raised awareness on the negative health impacts of tobacco use, especially to the internal organs. Graphic and emotionally evocative advertisements, especially those that have an impact on the family, have greater potential to motivate Samoans to quit.